2011
DOI: 10.1111/j.1365-277x.2011.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustained benefits of a community dietetics intervention designed to improve oral nutritional supplement prescribing practices

Abstract: The community dietetics intervention improved ONS prescribing practices by GPs and nurses, in accordance with best practice guidelines, without increasing expenditure on ONS during the year after intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 13 publications
(34 reference statements)
1
21
0
Order By: Relevance
“…These studies were conducted in the US (20, 21, 48), Ireland (44, 45), and Ethiopia (46). In all six studies, nutrition and general counseling skills of health workers improved after nutrition training.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies were conducted in the US (20, 21, 48), Ireland (44, 45), and Ethiopia (46). In all six studies, nutrition and general counseling skills of health workers improved after nutrition training.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven pre–post-intervention studies on nutrition training of health workers were conducted in Australia (37), South Africa (38), Gambia (39), UK (40, 41), Sweden (42), Denmark (43), Ireland (44, 45), Ethiopia (46), US, and Zambia (24). In all these studies, management practices and competence of health workers improved after the intervention compared to pre-nutrition training intervention levels.…”
Section: Resultsmentioning
confidence: 99%
“…Interventions to improve nutritional status in long-term care facilities have included education programs [13,14], provision of snacks and/or oral supplements [15-20], and improvement of mealtime ambience and assistance [21-23]. Relatively little attention, however, has been paid to the food provided, although nutritional analysis has shown that such food is typically high in saturated fat, salt, and added sugars, with low levels of starchy carbohydrate and fiber [24-27].…”
Section: Introductionmentioning
confidence: 99%
“…In Ireland, Kennelly et al (37,38) also found a positive effect on nutritional care practices in a study where fiftythree community nurses and twenty private nursing home staff nurses were trained to screen patients using the Malnutrition Universal Screening Tool and to manage malnutrition. Six months after the educational programme, changes to practice included weighing patients more frequently, providing simple dietary advice to people at malnutrition risk, and clinical justification for the use of oral nutritional supplements (37,38) .…”
Section: Addressing Unmet Educational Needsmentioning
confidence: 99%
“…Six months after the educational programme, changes to practice included weighing patients more frequently, providing simple dietary advice to people at malnutrition risk, and clinical justification for the use of oral nutritional supplements (37,38) . In Denmark, Pedersen et al (24) investigated outcomes of nurse nutrition education not only on nursing practice, but also on patient experience and knowledge.…”
Section: Addressing Unmet Educational Needsmentioning
confidence: 99%